(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
The study of Uzbek and Karakalpak linguistic words is examined in this scientific article, which looks at terminological writings on linguistic terminology produced between 1920 and the present, including research articles, scientific collections, monographs, and other publications.